2021
DOI: 10.1111/1365-2435.13889
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic thermal fluctuations can be burden or relief for an ectotherm depending on fluctuations’ average and amplitude

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 88 publications
1
31
0
Order By: Relevance
“…However, Roast et al (1999) did not measure feeding in their study, and therefore the direct link between respiration and feeding rates in N. integer remains unclear. In studies using the blue mussel Mytilus, it was shown that respiration and feeding are two different functional traits, which at times are decoupled from each other, suggesting that they should be compared with caution (Vajedsamiei et al, 2021).…”
Section: Sex-specific Ingestion Rates Under Constant Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Roast et al (1999) did not measure feeding in their study, and therefore the direct link between respiration and feeding rates in N. integer remains unclear. In studies using the blue mussel Mytilus, it was shown that respiration and feeding are two different functional traits, which at times are decoupled from each other, suggesting that they should be compared with caution (Vajedsamiei et al, 2021).…”
Section: Sex-specific Ingestion Rates Under Constant Temperaturesmentioning
confidence: 99%
“…For instance, population growth rates of a green alga under fluctuating temperatures could be sufficiently predicted by non-linear averaging using a TPC measured at constant temperatures (Bernhardt et al, 2018). Another study on the bivalve Mytilus, combining two experiments at different time scales, could predict long-term performance at fluctuating temperatures on the basis of short-term functioning (feeding) measured at constant temperatures using nonlinear averaging (Vajedsamiei et al, 2021). These studies also confirm the theory based on Jensen's Inequality that performance is smaller in fluctuating compared to constant temperatures (of the same mean) when fluctuations range in the concave part of the generally non-linear, unimodal TPC (Supplementary Box 1; Jensen, 1906).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conjunction of atmospheric and oceanographic processes caused marine heatwaves, which defined as long-term high surface temperature of ocean (Hobday et al, 2016;He et al, 2021). Ongoing ocean climate warming imposed more challenges of shallow-water ectotherms, such as shellfish, being exposed to beyond-optimal growth temperatures (Vajedsamiei et al, 2021). Lassoued et al (2021) pointed out that the impact of temperature on the metabolism and growth of marine organisms is an important driving stressor for their adaptation and warming of ocean would affect all their physiological activities to a large extent (Lassoued et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, some fluctuations and cycles can mimic the mean conditions expected due to ongoing ocean warming or acidification, which can precondition resident taxa to greater tolerance (Pansch et al, 2014;Vargas et al, 2017). In all cases, environmental variability can lead to periods where environmental conditions are favorable (Cornwall et al, 2014;Wahl et al, 2018;Vajedsamiei et al, 2021), and variability has therefore been proposed to also provide temporal refugia in a future ocean.…”
mentioning
confidence: 99%